The distribution of Apis laboriosa revisited: range extensions, biogeographic affinities, and species distribution modelling - Otis, Gard W.; Huang, Man-Juan; Kitnya, Nyaton; Sheikh, Umer Ayyaz Aslam; Faiz, Abu ul Hassan; Phung, Chinh H.; Warrit, Natapot; Peng, Yan-Qiong; Zhou, Xin; Oo, Hlaing Min; Acharya, Namoona; Devkota, Kedar (Frontiers in Bee Science, 2024)
Apis laboriosa, the Himalayan giant honeybee, inhabits the foothills of the Himalaya and neighboring mountainous regions. Here we revise its distribution in light of recent reports and discoveries. Several gaps in its range detected in previous studies have been filled with our more extensive data set. The range now extends from longitude 105.9°E in Cao Bang, Vietnam, in the east to 74.4°E in the Pir Panjal Range of western Himalaya, a linear distance of 3300 km, and from latitude 19.2°N in Nghe An, Vietnam and 20.1°N in Chiang Mai, Thailand to 34.8°N in Azad Jammu and Kashmir-Pakistan, with the most notable new localities in northeastern Vietnam, central Myanmar, northern Thailand, and AJK-Pakistan. The species generally occurs at lower elevations in the eastern part of its range than in Nepal, northern India, and the border region between India and Pakistan. Nearly all of the new localities in mainland Asia are within the range predicted by our species distribution modelling. We discuss the documented range extensions, review the terrestrial ecoregions in which the species occurs, contrast our species distribution model with a previous one, and highlight the remaining regions that may harbor this spectacular honey bee species.